2005
DOI: 10.1111/j.1365-2125.2005.02553.x
|View full text |Cite
|
Sign up to set email alerts
|

Tadalafil pharmacokinetics in healthy subjects

Abstract: Aims To characterize tadalafil plasma pharmacokinetics in healthy subjects following single and multiple doses. Methods Noncompartmental parameters were calculated for healthy subjects receiving a single 2.5–20‐mg tadalafil dose in 13 clinical pharmacology studies. An integrated statistical analysis of results in 237 subjects provided global averages and an assessment of effects of body mass index (BMI), age, gender and smoking status. Diurnal variation, food effects and proportionality of exposure to dose wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
205
0
6

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 240 publications
(222 citation statements)
references
References 21 publications
(23 reference statements)
8
205
0
6
Order By: Relevance
“…Among the patients who had the opportunity to try a cycle of therapy with tadalafil, 66-90% decided to continue their treatment with tadalafil, or switch to tadalafil. Patients on tadalafil may be less concerned about the time between dosing and intercourse, likely because of longer period of responsiveness for tadalafil 11 and the drug can be taken without regard to food intake, 13 in contrast to sildenafil and vardenafil, for which heavy-fat meals have been shown to decrease the extent and slow the rate of absorption. 14,41 The fact that convenience, simplicity and naturalness are traits that men value in an ED treatment 32 could, therefore, have contributed to more tadalafil patients being satisfied with their treatment, thereby resulting in less patients switching from tadalafil, as compared with sildenafil or vardenafil.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the patients who had the opportunity to try a cycle of therapy with tadalafil, 66-90% decided to continue their treatment with tadalafil, or switch to tadalafil. Patients on tadalafil may be less concerned about the time between dosing and intercourse, likely because of longer period of responsiveness for tadalafil 11 and the drug can be taken without regard to food intake, 13 in contrast to sildenafil and vardenafil, for which heavy-fat meals have been shown to decrease the extent and slow the rate of absorption. 14,41 The fact that convenience, simplicity and naturalness are traits that men value in an ED treatment 32 could, therefore, have contributed to more tadalafil patients being satisfied with their treatment, thereby resulting in less patients switching from tadalafil, as compared with sildenafil or vardenafil.…”
Section: Discussionmentioning
confidence: 99%
“…PDE-5 inhibitors differ mainly in half-life (that is, sildenafil and vardenafil B4 h and tadalafil B17.5 h), known duration of action and dietary effects on absorption. [13][14][15] In ED, where the patients' subjective perception is very important, the objective of treatment should not only be 'organ focused', that is, facilitating the erection, but should also be 'patient-outcome oriented'. Patients' satisfaction with sexual intercourse, their overall sex lives and ED treatments may represent reliable predictors of key patient-related treatment outcomes, in addition to pharmacological efficacy and safety.…”
Section: Introductionmentioning
confidence: 99%
“…27 A sublingual preparation of sildenafil has been developed, and this will not be affected by food. An initial study with sublingual sildenafil (20 mg) has shown that the mean onset of action was 15.5 min and lasted for an average of 40 min with 13/20 of subjects with ED achieving erections.…”
Section: Pharmacokineticsmentioning
confidence: 99%
“…7) In contrast, tadalafil has the advantage of once a day dosing compared to sildenafil's three times a day dosing, with implications for patient convenience and compliance. 6,8) Therefore, a transition from sildenafil to tadalafil has been frequently tried in stable patients with PAH. 3,8) In humans, sildenafil is eliminated predominantly by hepatic metabolism and is converted to an active metabolite, N-desmethyl sildenafil, with properties similar to the parent drug.…”
mentioning
confidence: 99%
“…3,4) That is, sildenafil has a fairly short half-life of about 4-5 h, whereas tadalafil has a long half-life of about 17.5 h in healthy subjects. 5,6) The short half-life of sildenafil makes it the drug of choice in patients with more severe cardiovascular disease, allowing early use of supportive treatment if an adverse clinical event occurs. 7) In contrast, tadalafil has the advantage of once a day dosing compared to sildenafil's three times a day dosing, with implications for patient convenience and compliance.…”
mentioning
confidence: 99%